Contributions of Three Starch Branching Enzyme Isozymes to the Fine Structure of Amylopectin in Rice Endosperm - Sawada, Takayuki; Itoh, Mizuho; Nakamura, Yasunori (Frontiers in Plant Science, 2018)
It is known that three starch branching enzyme (BE) isozymes; namely, BEI, BEIIa, and BEIIb, are involved in starch biosynthesis in rice endosperm. Past in vivo and in vitro studies have suggested that each BE isozyme plays a distinct role in forming the amylopectin fine structure. To reveal more in details their roles, we prepared the DNA constructs in which all the possible combinations of expressions of three BE isozymes were suppressed in developing rice endosperm. Analysis of the chain-length distributions of amylopectin produced under inhibition of various combinations of BE isozyme activities confirmed contributions of individual BE isozymes to the fine structure of amylopectin in rice endosperm. Among these isozymes, the impact of loss of BEIIb activity on the amylopectin fine structure was most remarkable, indicating that BEIIb plays a specific role in the synthesis of short chains of DP6-13. The contribution of BEI to the amylopectin synthesis was not clear when only the activity of BEI was reduced, whereas it was clearly assessed when activities of both BEI and BEIIb were severely inhibited. The intermediate chains of DP11-22 were markedly depleted in the ΔBEI/BEIIb line compared with the ΔBEIIb line. The result indicates that BEI plays a distinct role in the synthesis of these intermediate chains. Although no substantial change in the chain profile of amylopectin was detected in the ΔBEIIa line, the role of BEIIa could be decided by analyzing the amylopectin fine structure from the ΔBEI/BEIIa/BEIIb line by comparing that from ΔBEI/BEIIb line. The results strongly suggest that BEIIa supports the role of BEI, rather than that of BEIIb, by forming intermediate chains of DP11-22. In addition, we also presented the new possibility that BEIIa is involved in the formation of starch granules in rice endosperm because the onset temperature for gelatinization of starch granules in the ΔBEIIa/BEIIb line was significantly higher than that in the ΔBEIIb line. In summary, the present study shows the distinct roles of BEI, BEIIa, and BEIIb in the synthesis of amylopectin in developing rice endosperm.